(untitled) (Journal of Misan Researches, 2025)
God, the wise Creator, has revealed the Noble Qur’an to all people in different languages, colors, and environments, and people have stood by different and different positions, including the approved believer, and among them is the quarreling liar, and these two different positions called from the Great Qur’an to address each group with the appropriate discourse And it suits it from a style, and the section is one of the most important and greatest methods that God directed in the Qur’an for the Prophet (PBUH) and for the believers, and for the disbelievers who are ungrateful and unjust. , And to refute Suspicions, and to establish an argument against them, and to emphasize the news in which the sections appeared. And the style of the section in the Holy Qur’an is one of the most common and widely used methods of miracles, and it is the most widespread in the Qur’an. The Qur’an has opened many chapters in the oath; 40%), which indicates the importance of this method, and due to the vow of rhetorical studies in it, I have examined it rhetorically, studying the term section, the intended meaning, I monitored its images, and I clarified the aspects of its rhetorical beauty, its artistic functions, its purposes, and tracked the opinions of rhetoric and interpreters in many of those Pictures, and discussed their opinions on them. This research came in a preface, two articles, and a conclusion. The preface made it an introduction to the study of the concept of the department, and the most important features of the department’s linguistic, rhetorical, and literary, and the first topic: It made it a theoretical study, so I dealt with the section with language, terminology, rhetoric of the department and its technical secrets. As for the second topic: I made it applied, in which the verses of the section in "Amma’s Part" were analyzed in terms of the verb of the oath, the oath with it, the oath and its answer, and the oath’s rhetoric. The research reached a set of results, which I placed at the end of the research.